PENGARUH PRODUK WISATA DAN HARGA TERHADAP KEPUASAN WISATAWAN DI TAMAN MINI INDONESIA INDAH JAKARTA TIMUR - Nova Eviana; Afridah Intan (LPPM and Travel Operation Department Universitas Asa Indonesia, 2018)
Tourists satisfaction is a post-purchase behavior towards the product or image associated with a particular tourist attraction. It is an important variable that has been studied widely in the tourism sector. In the concept of marketing mix, tourism products and prices are two variables that affect tourists satisfaction after visiting a tourist attraction. In the midst of the emergence of various new tourist attractions, it encourages competition. Therefore, it is important for tourist attraction managers to formulate strategic policies to manage tourism products and set competitive prices. This study aims to determine the effect of tourism product variables and prices on tourist satisfaction at Beautiful Indonesia in Miniature Park, as one of the leading tourist attractions in Jakarta. The research analysis was carried out using multiple linear regression. The results of the study indicated that the price variable solely has an effect on tourist satisfaction, as well as the variable contribution of tourism products and the price variable of 13.5% on tourist satisfaction.